1989
DOI: 10.1111/j.1528-1157.1989.tb05449.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Frequency and Major Life Events in Epilepsy

Abstract: A group of 18 patients with chronic epilepsy were followed in an outpatient clinic for 1-6 years. Month-by-month seizure records were kept and the response to treatment was systematically explored. The present study was prompted when three patients became seizure-free, apparently in response to major life events (marriage, parenthood, and retirement) rather than to changes in treatment. All the subjects were interviewed in their own homes with a companion, friend, or relative present. The interview was based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…This suggests that personality characteristics are the main factors influencing general well-being. Thus, for these patients, psychological therapy and treatment should increase their general well-being and their quality of life (17). It was reported that psychic stimulation predisposes epilepsy to patients with seizure attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that personality characteristics are the main factors influencing general well-being. Thus, for these patients, psychological therapy and treatment should increase their general well-being and their quality of life (17). It was reported that psychic stimulation predisposes epilepsy to patients with seizure attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty; one graduated from college, 36 from senior middle school, 53 from junior middle school, and 7 from primary school. Patients had had seizures for an average of 17.2 years (range, 2 months-30 years). Eighty-five of the case patients had had epilepsy for at least 1 year.…”
mentioning
confidence: 99%
“…In questionnaire studies, stress is endorsed as a trigger, or precipitant, by more than 50% of people with epilepsy [20,23], while major life events are associated with seizure exacerbation in 8% to 50% of patients [6,12,24,25]. In prospective diary studies, both daily stress and stressful life events have been linked to increased seizure frequency [7,13,17,26,27]. For example, Temkin and Davis [26] and Haut et al [7] reported that risk of seizure increased in relation to increases in reported daily stress levels, while Neugebauer [17] showed that stressful major life events led to an increase in seizure occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of stressful life events has been studied in relation to seizure frequency 21 , epilepsy onset 22 and in studies comparing people with epilepsy with people with non-epileptic attack disorder 19,[23][24][25] . Stressful life events have also been proposed to have an epileptogenic effect in addition to being associated with psychopathology 26 .…”
Section: Introductionmentioning
confidence: 99%